2004
DOI: 10.1074/jbc.m407085200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Isoforms Differentially Phosphorylate Human Choline Acetyltransferase Regulating Its Catalytic Activity

Abstract: Choline acetyltransferase (ChAT) synthesizes acetylcholine in cholinergic neurons; regulation of its activity or response to physiological stimuli is poorly understood. We show that ChAT is differentially phosphorylated by protein kinase C (PKC) isoforms on four serines (Ser-440, Ser-346, Ser-347, and Ser-476) and one threonine (Thr-255). This phosphorylation is hierarchical, with phosphorylation at Ser-476 required for phosphorylation at other serines. Phosphorylation at some, but not all, sites regulates bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 49 publications
(53 reference statements)
2
29
0
1
Order By: Relevance
“…We showed previously that phosphorylation of ChAT by protein kinase C or calcium/calmodulin‐dependent protein kinase II alters ChAT enzyme activity, indicating that ChAT function is influenced by dynamic phosphorylation (Dobransky et al . , , , ). Phosphorylation by tyrosine kinases can regulate protein stability of multiples members of the extracellular signal‐regulated kinase signaling pathway through the ubiquitin–proteasome system (Nguyen et al .…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that phosphorylation of ChAT by protein kinase C or calcium/calmodulin‐dependent protein kinase II alters ChAT enzyme activity, indicating that ChAT function is influenced by dynamic phosphorylation (Dobransky et al . , , , ). Phosphorylation by tyrosine kinases can regulate protein stability of multiples members of the extracellular signal‐regulated kinase signaling pathway through the ubiquitin–proteasome system (Nguyen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The short‐term exposure to C3d induces high levels of ChAT activity and may indicate a novel mechanism of action. It has previously been shown that the ChAT protein can be phosphorylated and that phosphorylation may serve as an important regulator of its catalytic activity (Dobransky and Rylett, 2003, 2005; Dobransky et al, 2004). Furthermore, putative MAPK binding sites have been identified on the ChAT protein, making it possible that the activation of MAPK by NCAM, as shown in Figure 4, is acting to phosphorylate the ChAT protein and thereby increase ChAT activity.…”
Section: Discussionmentioning
confidence: 99%
“…Choline acetyltransfase phosphorylation in neurons is mediated predominantly by PKC at Ser-476 (required for phosphorylation by PKC at other serine residues to proceed), with PKC activation increasing phosphorylation at Ser-440 and enhancing choline acetyltransferase activity [54].…”
Section: Cholinergic Systemmentioning
confidence: 99%